Pengaruh Pass And Move Training terhadap Peningkatan Kemampuan Passing dan Control Atlet Sepak Bola U-15 di Akademi R19 Kendal Tahun 2022 - Riswanto, Adi; Sudarmono, Martin (Indonesian Journal for Physical Education and Sport, 2023)
The aim of the study was to determine the effect of pass and move training on improving the passing and control abilities of U-15 football athletes at the Kendal R19 Academy. The research method uses experimental research with a population and sample of 20 athletes. The results of the first hypothesis research obtained were 19.304 > t table 2.093 with a percentage increase of 33% so that there was an increase in passing ability in the U-15 football athlete at the Kendal Academy of R19. The second hypothesis is that the t value is 9.037 > t table 2.093 with a percentage increase of 28% so that there is an increase in the ability to control the U-15 football athletes at the Kendal Academy of R19. In conclusion, there is an effect of pass and move training on passing ability in U-15 soccer athletes at Kendal R19 Academy. There is also the effect of pass and move training on the control ability of U-15 soccer athletes at the Kendal R19 Academy. So that pass and move training can be a training reference that can improve the athlete's passing and control abilities.